Effective Communication in Muslim Families: A Solutive Study on Syiqaq Conflict in an Islamic Perspective - Algifari, Abidar; Hikmatullah, Hikmatullah (STAINI Press, 2026)
Conflicts in the family (syiqaq) are often triggered by poor communication patterns between family members. Ineffective communication leads to misunderstandings, emotional tension, and household disintegration. In fact, communication in the family ideally takes place reciprocated, both from parent to child, from child to parent, and between siblings. One of the communication patterns that is still common in families is stimulus-response communication, but this model is not enough to build true emotional closeness. This research is a qualitative research with a library research approach. Primary data is obtained from books on family communication, while secondary data comes from scientific articles, journals, and documents related to communication in an Islamic perspective. The analysis was carried out in a descriptive-qualitative manner with a normative approach. The results show that interactional communication patterns, where both parties are active and creative in conveying and interpreting messages, tend to create more dynamic and communicative relationships. From an Islamic perspective, communication values such as qawlan karima, qawlan layyina, and qawlan sadida are important foundations in creating ethical, empathetic, and effective communication. It can be concluded that communication built on Islamic principles is not only able to prevent syiqaq, but also becomes the main foundation in forming harmonious and sustainable family resilience.